FAKTOR PENDUKUNG STRATEGI PEMBELAJARAN PADA KETERAMPILAN VOKASIONAL TERNAK AYAM PETELUR BAGI PPKS PENYANDANG DISABILITAS MENTAL DI SENTRA DHARMA GUNA BENGKULU - Suhanti, Nadila Putri; Sofino, Sofino; Ulfasari, Nia (IKIP Siliwangi, 2025)
The purpose of this study is to determine the supporting factors for learning strategies in laying hen vocational skills for social welfare service users (PPKS) at the Dharma Guna Center in Bengkulu. Data collection techniques using interview, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Data validity was ensured using technique triangulation, source triangulation, and time triangulation. The research results show that the supporting factors for the learning strategy in laying hen vocational skills at the Dharma Guna center are the healthy physical condition of the PPKS, enabling them to participate in laying hen vocational skills activities, and external factors such as the competence of instructors in the field of animal husbandry, which affects the smooth running of learning, good interaction between managers, instructors, and PPKS, family support in the form of providing motivation to PPKS to encourage them to participate enthusiastically in skills activities, adequate facilities and infrastructure, and sufficient funding for the smooth running of the laying hen vocational skills program.